Health anxiety and related factors among the rural population : A cross-sectional study in China - Jiang, Zhihui; Cao, Gaohui; Suomi, Reima; Zha, Daolin (Sage, 2026)
This study investigated the prevalence and correlates of health anxiety among rural populations in China, due to the unique socio-economic challenges in these areas, such as limited healthcare access. A sample of rural residents (N = 909) was analyzed to identify key predictors of health anxiety, such as age, education level, living type, anxiety sensitivity, and perceived information overload. Results indicated that older individuals and those with lower educational levels exhibited significantly higher levels of health anxiety. Furthermore, living alone was associated with increased health anxiety, while anxiety sensitivity and perceived information overload were found to exacerbate anxiety levels. These findings highlight the critical need for tailored interventions aimed at mitigating health anxiety in rural areas, thereby contributing to improved mental health outcomes and overall well-being.